Improving Students’ Writing Ability By Using Answer Garden Application As A Brainstorming Media - Salsabilah , Nada Maharani (National Multidisciplinary Sciences, 2023)
In improving the quality of education, the need for adaptation between knowledge and everyday life. One of the most used skills in all aspects is writing. Through writing activities, one can express his thoughts in the form of concrete manifestations. Similarly, with students, writing aims to train their ability to think cognitively. But the problem is that students often feel hopeless before they start because they are confused about where to start. Hence the use of the Answer Garden application can be a solution in making interactive learning in getting feedback ideas from each student. This study uses the Classroom Action research (CAR) method with 2 cycles. Each cycle was held in 1 meeting and the subjects were students of Class X-B in SMA Muhammadiyah Jember. The study used 80 as the criteria of success of the students’ writing. This study showed an increase of 53.4% in students ' writing skills. By doing the preparation correctly, the implementation of this application will be successful so that the learning objectives will be achieved.